1997
DOI: 10.1177/026921639701100208
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the use of sedatives in a hospital support team and in a hospice

Abstract: This study examines how frequently and for what indications sedatives are prescribed in a hospital support team and in a hospice. We also looked at the survival of sedated patients from the date of admission and from the start of sedation. Overall 26% of patients were prescribed sedatives in order to sedate them (31% at the hospice and 21% at the hospital) and 43% of patients were given sedatives for symptom control (67% at the hospice and 21% at the hospital). Sedated patients survived for a mean of 1.3 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
2
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 6 publications
11
118
2
11
Order By: Relevance
“…The current literature refers to palliative sedation as terminal sedation and has focused on defining it, determining how often refractory symptoms occur in patients with advanced cancer, and discussion of the types of medications used to induce sedation (Chater, et a1., 1998;Cherny & Portenoy, !994;Fainsinger, Miller, Bruera, Hanson & Maceachern, 1991;Green & Davis, 1991; Morita, Inoue & Chihara, 1996; stone, Phillips, spruyt & waight, 1997;Ventafridda, Ripamonti, Deconno, Tamburini & Cassileth, 1990 (Bonica, 1985;Daut & Cleeland , lg82 (Bruera, Chadwick, Weinlick & Macdonald, 1987;Lawlor, Fainsinger, Bruera, 2000;Massie, Holland & Glass, 1983). Furthermore, in a canadian survey ofcancer patients (n:913), 94 % ofrespondents reported L 4 experiencing more than one symptom (Ashbury,Findlay,Reynolds & McKerracher,1g98).…”
Section: Dedicationmentioning
confidence: 99%
“…The current literature refers to palliative sedation as terminal sedation and has focused on defining it, determining how often refractory symptoms occur in patients with advanced cancer, and discussion of the types of medications used to induce sedation (Chater, et a1., 1998;Cherny & Portenoy, !994;Fainsinger, Miller, Bruera, Hanson & Maceachern, 1991;Green & Davis, 1991; Morita, Inoue & Chihara, 1996; stone, Phillips, spruyt & waight, 1997;Ventafridda, Ripamonti, Deconno, Tamburini & Cassileth, 1990 (Bonica, 1985;Daut & Cleeland , lg82 (Bruera, Chadwick, Weinlick & Macdonald, 1987;Lawlor, Fainsinger, Bruera, 2000;Massie, Holland & Glass, 1983). Furthermore, in a canadian survey ofcancer patients (n:913), 94 % ofrespondents reported L 4 experiencing more than one symptom (Ashbury,Findlay,Reynolds & McKerracher,1g98).…”
Section: Dedicationmentioning
confidence: 99%
“…Napjainkban is megtapasztalható a súlyos dyspnoé-ban szenvedő betegek kezelését végző orvosok opioidok használatával szembeni aggodalma, azok légzésdepresz-sziót okozó hatása miatt. Azonban számos vizsgálat igazolta, hogy a nehézlégzés enyhítésére használt opioidok nem csökkentik a betegek élettartamát, nem ronják élet-kilátásaikat [22,23,24,25]. A 2. táblázat összefoglalja a fulladás tüneti kezelésére használható opioidok adagolá-sát és dózisát különböző súlyosságú és jellegű fulladás esetén opiátkezelésben még nem részesült és opiátot már használó betegek esetén.…”
Section: Légszomjunclassified
“…Chan et al found that higher doses of opioids and anxiolytic medications used in withdrawal of life support were not associated with a decreased time from withdrawal of life support to death [67]. Other studies found that survival time after withdrawal of mechanical ventilation in the last week of life was unrelated to the dose of prescribed morphine [68][69][70]. Of numerous studies that provided information on oxygen saturation or arterial blood gases, only one investigation reported any changes in oxygenation with use of opioids [1].…”
Section: Recommendations For Opioid Usementioning
confidence: 99%